Bumps and bridges on the road to responsible sharing of clinical trial data. (February 2014) - Berlin, Jesse A; Morris, Sandra; Rockhold, Frank; Askie, Lisa; Ghersi, Davina; Waldstreicher, Joanne
Background: Sharing data from clinical trials could assist with the advancement of science and medicine, potentially providing a better understanding of both the benefits and risks of medicines and other treatments. Sharing data also allows for questions to be addressed at the meta-analysis level that cannot be addressed within individual studies. Purpose: In this article, we offer some practical recommendations that will allow researchers to readily combine datasets from different studies and sources, thereby enabling meta-analyses that could have significant impact on advancing medicine. Methods: The authors relied on their collective experience in the conduct and reporting of clinical trials to define the areas of potential concern related to responsible sharing of clinical trial data. We conducted a review of the literature and engaged in an iterative consensus-building process. Results: To further the goal of responsible sharing of clinical trial data, collaboration on a consistent set of data standards and methods across both industry and academia is sorely needed. Protection of participant privacy is a paramount principle. The additional questions of who maintains, funds, and oversees databases of participant-level data will be important to resolve. Requiring researchers to register their requests for participant-level data and to provide details of their intended research would allow others to evaluate the proposed research plan, consistent with the principles of science and transparency. Limitations: The recommendations represent the views of the individual authors. We recognize that other approaches to data sharing that have been advocated are also based on sound ethical and scientific principles.